An Analysis of Efficiency and Loan Loss Provisioning Behavior in Chinese Banking - CHEN, SIYU (2017)
This paper investigates Loan Loss Provision (LLP) determinants from four perspectives: income smoothing, business cycle, capital management and cost efficiency, applying the stochastic frontier analysis (SFA) methodology to derive X-efficiency scores and the system generalized method of moments (SGMM) methodology to analyze the relationships between selected variables and LLP based on 106 Chinese commercial banks over the period from 2011 to 2016. The empirical findings demonstrate the existence of pro-cyclicality LLP management in Chinese banks, however fail to support income smoothing and capital management hypothesis. Also, cost efficiency is found to be negatively correlated with loan loss provision at 10% confidence level.